2007
DOI: 10.1016/j.amjcard.2006.10.064
|View full text |Cite
|
Sign up to set email alerts
|

Design and Baseline Characteristics of the Simvastatin and Ezetimibe in Aortic Stenosis (SEAS) Study

Abstract: Aortic valve stenosis and atherosclerotic disease have several risk factors in common, in particular, hypercholesterolemia. Histologically, the diseased valves appear to have areas of inflammation much like atherosclerotic plaques. The effect of lipid-lowering therapy on the progression of aortic stenosis (AS) is unclear, and there are no randomized treatment trials evaluating cardiovascular morbidity and mortality in such patients. The Simvastatin and Ezetimibe in Aortic Stenosis (SEAS) Study is a randomized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(110 citation statements)
references
References 18 publications
2
104
1
3
Order By: Relevance
“…More recently, the Simvastatin and Ezetimibe in Aortic Stenosis (SEAS) trial revealed that combined therapy with simvastatin ezetimibe resulted in a significant reduction of the risk of ischemic cardiovascular events, mainly fewer CABG procedures. However, no significant difference was detected in the secondary outcome of aortic-valve-related events between the simvastatin ezetimibe and control groups 48) . Otherwise, the results of the SEAS trial highlighted the growing debate of whether ezetimibe administration in addition to a statin to achieve more marked lowering of the serum LDL cholesterol level might increase the incidence of cancer.…”
Section: Casementioning
confidence: 98%
See 1 more Smart Citation
“…More recently, the Simvastatin and Ezetimibe in Aortic Stenosis (SEAS) trial revealed that combined therapy with simvastatin ezetimibe resulted in a significant reduction of the risk of ischemic cardiovascular events, mainly fewer CABG procedures. However, no significant difference was detected in the secondary outcome of aortic-valve-related events between the simvastatin ezetimibe and control groups 48) . Otherwise, the results of the SEAS trial highlighted the growing debate of whether ezetimibe administration in addition to a statin to achieve more marked lowering of the serum LDL cholesterol level might increase the incidence of cancer.…”
Section: Casementioning
confidence: 98%
“…Peto R analyzed the incidence of cancer in the subjects of the SEAS trial (mean follow-up, 4.1 years) with those of two currently ongoing large trials, the Study of Heart and Renal Protection (SHARP) (mean follow-up, 2.7 years) and the Improved Reduction of Outcomes: Vytorin Efficacy International Trial (IMPROVE-IT) (mean follow-up, 1.0 year). They concluded that the available results from these three trials did not provide any credible evidence of an adverse effect of ezetimibe on the incidence rate of cancer 48,49) . Non-clinical data obtained from chronic administration studies in 3 species and 2-year carcinogenicity studies in rats and mice conducted by Halleck M also suggest that ezetimibe is not carcinogenic 50) .…”
Section: Casementioning
confidence: 99%
“…Whether LDL-C lowering through dual inhibition of reduced cholesterol absorption and synthesis translates to enhanced clinical benefit for reducing CHD events awaits further assessment in longer term, outcome-based clinical trials (TABLE 4) [135][136][137]. During the next several years, the results of these CHD outcome studies will help to better clarify the clinical importance of the metabolic effects of ezetimibe, with respect to LDL-C lowering and beyond.…”
Section: Five-year Viewmentioning
confidence: 99%
“…The primary end point is mean change from baseline to 2 years in carotid intima-media thickness (IMT), using composite measures from the right and left far wall common carotid artery, carotid bulb, and internal carotid artery. The Simvastatin and Ezetimibe in Aortic Stenosis (SEAS) study 46) is the largest randomized trial to date in patients with asymptomatic, degenerative aortic stenosis. This 4-year study in 1,800 patients will evaluate the mortality and morbidity reduction with ezetimibe/simvastatin 10/40 mg vs placebo.…”
Section: Ongoing Surrogate and Clinical Outcome Trials With Ezetimibementioning
confidence: 99%